Where are we [compact disc] - Redman, Joshua (Blue Note, 2023)
Acclaimed saxophonist Joshua Redman's stunning Blue Note debut is one of his most compelling albums to date. It's a musical journey across the United States of America that also marks Redman's first-ever vocal album with the dynamic young singer Gabrielle Cavassa featured throughout along with a brilliant band comprised of pianist Aaron Parks, bassist Joe Sanders, and drummer Brian Blade.